The Effects of Agency Selling on Reselling on Hybrid Retail Platforms. Issue 4 (2nd October 2019) - Li, Qi; Wang, Quansheng; Song, Peijian
ABSTRACT: Numerous online retail platforms have begun to operate in a hybrid mode, which blends the use of a traditional reselling mode (operated by the platform owner) and increasingly prevalent agency-selling mode (operated by the affiliated agency sellers) to leverage internal and external resources. Two types of sellers interact and cooperate to improve the competitiveness of the hybrid platform in the online market. Although the hybrid mode is an inevitable trend that helps alleviate the burden of product expansion for reselling, reselling may also face sales cannibalization from agency selling. We empirically explore the effects of agency selling on reselling by using panel vector autoregression. Findings show that agency selling has a positive effect on reselling. The number of agency sellers may strengthen, whereas the market concentration of agency selling will weaken such effect. Furthermore, agency- selling participation is harmful to the positive effect of agency selling on reselling but is statistically marginally significant. These findings have important theoretical implications to enrich the two-sided market and extend the interorganizational relationship and coopetition theories. Moreover, our results also offer several crucial managerial implications for platform owners.